Investigation on RF Mems Switches: Designs, Fabrications and Measurements (International Journal of Scientific Research in Science and Technology, 2025)
The motivation for using radio frequency microelectromechanical systems (RF MEMS) technology for the control of microwave circuits and antennas is presented in this paper. A brief survey of currently used microelectronic RF switching technologies is presented. This is followed by an introduction to the fundamental characteristics of RF MEMS switches. The inherent advantages of these switches relative to semiconductor switches are discussed. Microwave circuit and system applications that could benefit from the use of RF MEMS switches are listed.